2016
DOI: 10.1089/can.2016.0024
|View full text |Cite
|
Sign up to set email alerts
|

Training and Practices of Cannabis Dispensary Staff

Abstract: Introduction: The proliferation of cannabis dispensaries within the United States has emerged from patient demand for the legalization of cannabis as an alternative treatment for a number of conditions and symptoms. Unfortunately, nothing is known about the practices of dispensary staff with respect to recommendation of cannabis strains/concentrations for specific patient ailments. To address this limitation, the present study assessed the training and practices of cannabis dispensary staff.Materials and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 24 publications
0
66
0
Order By: Relevance
“…However, the US Hemp Farming Act of 2018 legalized the cultivation and refinement of hemp and its constituents, thus beginning a trend of mass marketing for CBD products both legal and illegal (Hemp Production andthe 2018 Farm Bill, 2019;Mead, 2019). In states where cannabis has been approved for recreational and/or medical use, there are efforts to equip dispensary staff with scientific knowledge to make evidencebased recommendations, but these efforts are limited and often overshadowed by anecdotal understanding of CBD and other cannabinoids (Haug et al, 2016;Piermarini and Viswanath, 2019). Of major concern, CBD-labeled products have flooded the markets, including, but not limited to, inhalants, bath salts, cookies, ointments, and liquids, for human use.…”
Section: Reliability and Safety Of Cannabidiol Labeled Productsmentioning
confidence: 99%
“…However, the US Hemp Farming Act of 2018 legalized the cultivation and refinement of hemp and its constituents, thus beginning a trend of mass marketing for CBD products both legal and illegal (Hemp Production andthe 2018 Farm Bill, 2019;Mead, 2019). In states where cannabis has been approved for recreational and/or medical use, there are efforts to equip dispensary staff with scientific knowledge to make evidencebased recommendations, but these efforts are limited and often overshadowed by anecdotal understanding of CBD and other cannabinoids (Haug et al, 2016;Piermarini and Viswanath, 2019). Of major concern, CBD-labeled products have flooded the markets, including, but not limited to, inhalants, bath salts, cookies, ointments, and liquids, for human use.…”
Section: Reliability and Safety Of Cannabidiol Labeled Productsmentioning
confidence: 99%
“…Although more than 90% of dispensary staff in the United States reported providing advice to patients, only 20% had (unspecified) medical training and 13% had scientific training. 8 The medical advice that was given was often not evidence based.…”
mentioning
confidence: 99%
“…12 A survey describing the training of 55 individual cannabis dispensary staff reported that 20% of the survey participants received medical or scientific training related to marijuana but 94% provided specific cannabis advice to patients. 13 Based on postcourse feedback, residents who participated in our course now feel more confident in how to discuss cannabis with their patients and in their knowledge concerning fundamentals of pharmacokinetics and the endocannabinoid system, and they are more aware of the existing literature regarding cannabis use in psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%